Time Perception Test in IntelliCage System for Preclinical Study: Linking Depression and Serotonergic Modulation - Olga Sysoeva; Rauf Akhmirov; Maria Zaichenko; Ivan Lazarenko; Anastasiya Rebik; Nadezhda Broshevitskaja; Inna Midzyanovskaya; Kirill Smirnov (Diagnostics)
Background/Objectives:: The link between serotonergic modulation and depression is under debate; however, serotonin reuptake inhibitors (SRIs) are still the first-choice medicine in this condition. Disturbances in time perception are also reported in depression with one of the behavioral schedules used to study interval timing, differential-reinforcement-learning-of-low-rate, having been shown to have high predictive validity for an antidepressant effect. Here, we introduce an IntelliCage research protocol of an interval bisection task that allows more ecologically valid and less time-consuming rodent examination and provides an example of its use to confirm the previously reported acute effect of an SRI, clomipramine, on interval timing (increase in bisection point, D50). Methods: Wistar male rats (n = 25, five groups of 5–8) were trained in the IntelliCage to discriminate between short (1 s) and long (4 s) LED light stimuli by nose poking at the corresponding (left/right) side of the IntelliCage chamber to obtain a drink. When 80% of correct responses were reached, the intermediate durations of 1.7, 2.5, and 3.3 s were introduced. The number of left/right choices for each stimulus and interval timing parameters (bisection point, D50, and timing precision), derived from them, were compared after saline and clomipramine (7 mg/kg, i.p) intraperitoneal administration. Results: Rats successfully learned the task within about a week of training. The slightly increased D50 after clomipramine confirmed previous studies. Conclusions: The introduced protocol has potential to be applicable to preclinical research on depression and potentially other psychopathology, where time perception can be disturbed.